Diversity of macrochelid mites in natural and cultivated areas of São Paulo state, Brazil, with description of a new species of Holostaspella (Mesostigmata: Macrochelidae) and a key to the caelata group - Borges, Vinícius; Azevedo, Letícia Henrique [UNESP]; Castilho, Raphael De Campos; De Moraes, Gilberto José (Systematic and Applied Acarology Society, 2021)
The stable fly, Stomoxys calcitrans (L.), is one of the main pests of livestock in Brazil, especially in areas where cattle is raised next to sugarcane (Saccharum spp.) fields in which vinasse is used as a fertilizer. Knowledge about the predatory mites associated with this parasite in the field may be helpful in designing programs to control it biologically. Mites of the family Macrochelidae are known to attack fly immatures, and thus could be helpful in reducing the population of the stable fly in the field. The aim of this paper is to report the macrochelid species found in surveys conducted in northwestern São Paulo state, where the fly is known to be present, including a new species here described, Holostaspella paulista Borges & Azevedo sp. nov., to provide complementary descriptions of the other species collected, and to present a key to the caelata group of Holostaspella. In total, 2,946 macrochelid specimens were collected from 264 samples of soil-litter or soil-cow obtained from two areas of sugarcane plantations, a pasture area and a disturbed patch of the Atlantic Forest in 2018 and 2019. Four species of Macrocheles, two of Holostaspella and one of Glyptholaspis were identified. The predominant species was Macrocheles merdarius (Berlese).
Keywords: biological control; predator; soil mites; taxonomy